2020
DOI: 10.3390/ani10050898
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Neuroprotective Effects of Quercetin against Aflatoxin B1-Intoxicated Mice

Abstract: Aflatoxin B1 (AFB1) is a mycotoxin commonly present in feed, characterized by several toxic effects. AFB1 seems to have a neurotoxical effect that leads to memory impairment behavior. AFB1 toxicity involves the induction of the oxidative stress pathway, rising lipid peroxidation, and it decreases antioxidant enzyme levels. Hence, in our research, we wanted to evaluate the potential protective effects of quercetin 30 mg/kg in AFB1-mediated toxicity in the brain and the ameliorative effect on behavioral alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 64 publications
1
45
0
Order By: Relevance
“…As previously reported, MDA levels were determined to detect lipid peroxidation four days after administration of DNBS in colon tissue [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…As previously reported, MDA levels were determined to detect lipid peroxidation four days after administration of DNBS in colon tissue [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, being nonspecific, they also bind vitamins and trace elements, generating deficiencies [45][46][47]. Adding some plant-derived antioxidants in feed could be a better solution [48] to diminish the deleterious effects of mycotoxins on animal health. P450 cytochromes enzymes, mainly present in liver, intestinal tract, and kidney, play an important role in phase I biotransformation of xenobiotics, especially those belonging to the families 1 and 3 [49].…”
Section: Introductionmentioning
confidence: 99%
“…However, being nonspecific, they also bind vitamins and trace elements, generating deficiencies [ 45 , 46 , 47 ]. Adding some plant-derived antioxidants in feed could be a better solution [ 48 ] to diminish the deleterious effects of mycotoxins on animal health.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin has many biological functions including anti-oxidant, antiinflammatory, and immune-regulatory activities (17)(18)(19). Quercetin supplementation had been shown to attenuate D-Galactose-induced renal damage in rats and aflatoxin B1-induced neurotoxicity in mice through the inhibition of oxidative stress (20,21). A recent study also showed that quercetin supplementation could inhibit lipopolysaccharide (LPS)-induced inflammation in a proximal tubular cell line human kidney 2 (HK-2) cells which derived from normal human kidney (22).…”
Section: Introductionmentioning
confidence: 99%